Increasing Public Awareness Through the Innovation of the Jumantik Movement in Pucang Sewu Subdistrict Surabaya: Peningkatan Sadar Kesehatan Masyarakat Melalui Inovasi Gerakan Jumantik di Kelurahan Pucang Sewu Surabaya - Zahra Khania Putri; Tasya Putri Febriane; Mirza Nirmala Firdausi; Intania Widyantari Kirana (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Dengue Hemorrhagic Fever (DBD) is a public health problem that still frequently occurs in densely populated areas, including Pucang Sewu Village, Surabaya. Low public awareness of prevention and Mosquito Nest Eradication (PSN) efforts increases the risk of transmission of the disease. This community service activity aims to increase public knowledge and awareness through the innovation of the Jumantik (Juru Pemantau Larvae) Movement in RW 05. The implementation method includes socialization, counseling, and training in larva inspection by involving local Family Empowerment and Welfare (PKK) cadres. The results of the activity show an increase in community participation in larva inspection and the implementation of 3M (Draining, Covering, and Reusing used goods) Plus, which is marked by the formation of independent Jumantik cadres in each Neighborhood Association (RT). These findings indicate that the Jumantik Movement contributes to increasing public awareness of dengue fever prevention and supports the implementation of clean and healthy living behaviors in a sustainable manner.